DISSOLVING PULP FROM KENAF BY BIO-BLEACHING PROCESS - Susi Sugesty; Yusup Setiawan (Center for Pulp and Paper, 2013)
The kenaf taken from Malang-East Java was four to five months old and used as the raw material of dissolving pulp. Morphology and chemicals content of kenaf was analyzed based on Indonesian National Standard (SNI). Kenaf fibre has the fibre length average of 2.59 mm for stem and 3.63 mm for bast and it is classified on the long fiber, fibre length > 1.60 mm. It contains alpha cellulose in the amount of 45.45% for bast and 39.46% for stem. Kenaf was cut with the length of 3 to 5 cm to make chips. Before cooking, pre-hydrolyzed using water and dilute acid (0.4% H2SO4) was done to remove pentosan (hemicellulose) by soaking chips in water and 0.4% H2SO4 in the ratio of 1 : 5 at temperature of 135oC for 2 hours. The results was mixed with cooking liquor which contains Active Alkali (AA) of 16% and Sulfidity (S) of 28%. Ratio of raw material and cooking liquor was 1 : 5 at temperature of 160oC for 3 hours. Bleaching process was done in the five stages consisted of X0D0E0D1D2 (Xylanase, Oxygen delignification, Chlorine Dioxide, Oxygen Ectraction, Chlorine Dioxide 1st, Chlorine Dioxide 2nd). Bleaching process in the stage of X use xylanase enzyme (bio-bleaching). Every stage was washed with hot soft water up to neutral pH. Dissolving pulp was analyzed for brightness, alpha cellulose content and other chemicals content. Pulp viscosity is very high, which means that the pulp bleaching process is not much cause degraded cellulose Keywords: bio-bleaching, dissolving pulp, pre-hydrolyzed, kenaf, xylanase ABSTRAKKenaf berasal dari daerah Jawa Timur Malang - berusia empat sampai lima bulan dan digunakan sebagai bahan baku dissolving pulp. Morfologi dan komponen kimia kenaf dianalisis berdasarkan Standar Nasional Indonesia (SNI). Serat kenaf memiliki panjang serat rata-rata 2,59 mm untuk batang dan 3,63 mm untuk kulit pohon, termasuk kedalam kelompok serat panjang dengan panjang serat > 1,60 mm. Kenaf mengandung alpha selulosa sebesar 45,45% untuk kulit dan 39,46% untuk batang. Kenaf dipotong-potong dengan panjang 3 sampai dengan 5 cm. Sebelum pemasakan, dilakukan prahidrolisa menggunakan air dan asam encer (0,4% H2SO4) untuk melunakkan serpih kenaf dan membuat ikatan pentosan (hemiselulosa) menjadi lemah, dengan merendamnya dalam air dan 0,4% H2SO4 dengan rasio 1 : 5 pada suhu 135oC selama 2 jam. Selanjutnya dilakukan pemasakan dengan proses kraft menggunakan Alkali Aktif (AA) sebesar 16% dan sulfiditas (S) sebesar 28%. Rasio bahan baku dan larutan pemasak adalah 1 : 5 pada suhu 160oC selama 3 jam. Proses pemutihan pulp dilakukan dalam lima tahap terdiri dari X0D0E0D1D2 (Xilanase, Oksigen delignifikasi, Klorin dioksida, Oksigen Ekstraksi, Klorin dioksida 1, Klorin dioksida 2). Proses pemutihan pada tahap X menggunakan enzim xilanase yang dikenal dengan bio–bleaching. Setiap tahap dicuci dengan air panas sampai bersih. Dissolving pulp yang diperoleh dianalisis derajat cerah, kadar selulosa alfa dan komponen kimia lainnya sesuai SNI. Dissolving pulp mempunyai viskositas yang sangat tinggi, ini berarti bahwa proses pemutihan pulp tidak banyak menyebabkan terjadinya degradasi selulosa.Kata kunci: bio-bleaching, dissolving pulp, prehidrolisa, kenaf, xilanase